Construction of elliptic curve cryptography‐based authentication protocol for internet of things. Issue 4 (22nd March 2022) - Chhikara, Deepak; Rana, Saurabh; Mishra, Ankita; Mishra, Dheerendra; ,
Abstract: The advancement in the internet of things (IoT) is bringing changes in our daily lives. The widespread adoption of the IoT in a variety of areas sets the basis for smart living while also posing privacy and security concerns. Authentication and key agreement (AKA) protocol provides identity authentication for participants in a communication system and generates a temporary session key for participants to securely transmit messages. In addition to this, the adoption of smart cards adds a second line of defense in AKA protocols for IoT. To enhance the security of AKA protocols for IoT, many AKA protocols are proposed, but the majority of them fail to manage the balance between security and efficiency. To achieve both security and efficiency together for IoT, based on the elliptic curve public‐key cryptography, we design a three‐factor AKA protocol. We follow security analysis and efficiency analysis to analyze the security and efficiency. By comparing with related existing protocols, it is found that this protocol achieves security and efficiency attributes. The investigation shows that the protocol can meet key security requirements, consumes less computing resources, and is especially suitable for IoT scenarios with high security and efficiency.